CaMKII modulates memory destabilization by regulating the interaction of theta and gamma oscillations - Rossato, Janine I.; Gonzalez, Maria Carolina; Souza, Johseph P. G.; Radiske, Andressa; Apolinario, Gênedy; Baracho, Ana Luizi; Cammarota, Martín (Frontiers in Cellular Neuroscience, 2025)
Object recognition memory (ORM) allows animals to distinguish between novel and familiar items. When reactivated during recall in the presence of a novel object, a consolidated ORM can be destabilized and linked to that generated by the novel object through reconsolidation. The CA1 region of the dorsal hippocampus contributes to ORM destabilization and reconsolidation, with mechanisms involving theta/gamma cross-frequency coupling (hPAC) and synaptic plasticity modulation. Ca2+/calmodulin-dependent protein kinase II (CaMKII) is vital for hippocampus-dependent memory processing and has been associated with theta activity-dependent plasticity in dorsal CA1. However, the specific role of hippocampal CaMKII in the lasting storage of reactivated ORM remains unclear, and its potential impact on memory-related oscillatory activity has not been previously investigated. To explore these questions, we employed a combination of behavioral, electrophysiological, and pharmacological approaches at various stages of ORM processing, and found that CaMKII is not necessary for ORM recall or reconsolidation but does regulate novelty-induced ORM destabilization by modulating hPAC.